The Influence Of Innovative Human Resource Management On Faculty Members’ Productivity :A Study Among Private Universities In The UAE - Ahmad Farhan, Abedallah Farouq (2022)
The UAE’s higher education sector has experienced dramatic growth and undergone strategic changes over the last decade. One of the most significant changes concerns the increased focus given to faculty members’ productivity. The current research aims to examine the influence of innovative HRM practices, including innovative recruitment and selection, innovative training and development, innovative reward and compensation, and innovative performance appraisal on the productivity of faculty members working in private universities in the country. The study also examines the mediating role of organizational commitment and the moderating role of the entrepreneurial mindset.